RNA interference technology : from basic science to drug development - Appasani, Krishnarao (Cambridge University Press, 2005)
RNA Interference (RNAi) technology has rapidly become one of the key methods used in functional genomics. In this cutting-edge overview, the basic concepts of RNAi biology are discussed, as well as the current and potential applications, providing an invaluable reference for all those who need to understand this emerging technology.